Design and simulation of an underactuated finger mechanism for LARM Hand. Issue 3 (21st July 2015) - Ceccarelli, M.; Zottola, M.
SUMMARY: An underactuated mechanism is presented as a new finger design for improving grasp adaptability of LARM Hand fingers. Underactuation is discussed as a feasible solution through several design structures for finger adaptability to shape and size of objects to be grasped. The proposed underactuated solution for a new LARM finger is characterized through simulation results in ADAMS environment for operation feasibility and performance.